ANALISIS KELAYAKAN KOPERASI UNIT DESA DI DAERAH ISTIMEWA YOGYAKARTA - Abi Pratiwa Siregar; Jamhari Jamhari (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2013)
This research aims to (1) determine the financial performance of village unit cooperative/Koperausi Unit Desa (KUD) in Yogyakarta Special Region (2) determine the affecting factors of profit/selisih hasil usaha (SHU) (3) determine the institutional performance of village unit cooperative in Yogyakarta Special Region. The basic method used for this stufy is descriptive snalysis. The data used are the primary and secondary data. Data primary obtained through the interview whiledata secondary obtained through KUD’s annual report from 2011 untul 2012/ sampling method is purposive sampling, based on the highest profit value in each KUD in regency or city inYogyakarta Special region in 2012, any KUD in each regency or city taken 4 people respondents, 3 people of board organizer, and 1 inspector of each KUD. Method of analysis used financial rationanalysis to determine financial performance of village unit cooperation in Yogyakarta Special Region, multiple regression analysis to determine the affecting factors of profit and analysis efforts to determine tye institutional performance of village unit cooperative in Yogyakarta Special Region. The result showed that financial performance of village unit cooperative in Yogyakarta Special Region still low. The significant factors for affecting profit are business volume, dummy USP, dummy RMU, dummy electricity, and the number of members own capital, outside capital, total assets, dummy waserda, anda dummy saprotan are not significant factor for affecting profit. KUD in Yogyakarta Special Region having well-institution performance.